Remote Patient Management May Reduce All-Cause Mortality in Patients With Heart-Failure and Renal Impairment - Naik, Marcel G.; Budde, Klemens; Koehler, Kerstin; Vettorazzi, Eik; Pigorsch, Mareen; Arkossy, Otto; Stuard, Stefano; Duettmann, Wiebke; Koehler, Friedrich; Winkler, Sebastian (Frontiers in Medicine, 2022)
Background: Remote patient management (RPM) in heart failure (HF) patients has been investigated in several prospective randomized trials. The Telemedical Interventional Management in Heart Failure II (TIM-HF2)-trial showed reduced all-cause mortality and hospitalizations in heart failure (HF) patients using remote patient management (RPM) vs. usual care (UC). We report the trial’s results for prespecified eGFR-subgroups. Methods: TIM-HF2 was a prospective, randomized, controlled, parallel-group, unmasked (with randomization concealment), multicenter trial. 1538 stable HF patients were enrolled in Germany from 2013 to 2017 randomized to RPM (+UC) or UC. Using CKD-EPI-formula at baseline, prespecified subgroups were defined. In RPM, patients transmitted their vital parameters daily. The telemedical center reviewed and co-operated with the patient’s General Practitioner (GP) and cardiologist. In UC, patients were treated by their GPs or cardiologist applying the current guidelines for HF management and treatment. The primary endpoint was percentage of days lost due to unplanned cardiovascular hospitalizations or death, secondary outcomes included hospitalizations, all-cause and cardiovascular mortality. Results: Our sub analysis showed no difference between RPM and UC in both eGFR-subgroups for the primary endpoint (<60ml/min/1.73m²: 40.9% vs. 43.6%, p=0.1, ≥60ml/min/1.73m² 26.5% vs. 29.3%, p=0.36). In patients with eGFR<60ml/min/1.73m² one-year-survival was higher in RPM than UC (89.4% vs. 84.6%, p=0.02) with an incident rate ratio (IRR) 0.67 (p=0.03). In the recurrent event analysis HF hospitalizations and all-cause death were lower in RPM than UC in both eGFR-subgroups (<60ml/min/1.73m²: IRR 0.70, p=0.02; ≥60ml/min/1.73m²: IRR 0.64, p=0.04). In a cox regression analysis, age, NT-pro BNP, eGFR and BMI were associated with all-cause mortality. Conclusion: RPM may reduce all-cause mortality and HF hospitalizations in HF-patients with eGFR<60ml/min/1.73m². HF hospitalizations and all-cause death were lower in RPM in both eGFR-subgroups in the recurrent event analysis. Further studies are needed to investigate and confirm this finding.